Whole-Genome Sequencing as Tool for Investigating International Tuberculosis Outbreaks: A Systematic Review - van der Werf, Marieke J.; Ködmön, Csaba (Frontiers in Public Health, 2019)
Background Whole genome sequencing (WGS) can support the investigation of tuberculosis (TB) outbreaks. The technique has been applied to estimate the timing and directionality of transmission and to exclude cases from an investigation. This review assesses how WGS was applied in international outbreak investigations and discusses the advantages and challenges of the application of WGS. Methods Databases were searched for reports on international TB outbreak investigations. Information was extracted on: Why was WGS applied?; How was WGS applied?; Organisational issues; WGS methodology; What was learned/what were the implications of the WGS investigation?; and challenges and lessons learned. Results Three studies reporting on international outbreak investigations were identified. Retrospective WGS sequencing was performed in all studies and prospective typing in two to study TB transmission. In one study, WGS data were produced centrally (i.e. in one laboratory) and analysis was done centrally. In two studies, WGS data production was done in a decentralized manner and analysis was centralized in one laboratory. Three groups of professionals were involved: public health authorities, laboratory experts and clinicians. The reported WGS methodology applied differed between the studies in some aspects, e.g. sequencing platform; quality measures, percentage of the reference genome covered and the mean genomic coverage; analysis, use of a reference genome or de novo assembly; and software used for alignment and analysis. In all three studies, in-house scripts were used for variance calling and the single nucleotide polymorphism (SNP) approach was used for analysis. All outbreak investigation reports stated that WGS refuted suspected transmission events and provided supporting evidence for epidemiological data. Several challenges were reported of which most were not related to WGS. The only challenge related to WGS was the timeframe of getting WGS data if WGS is not routinely performed. Conclusions WGS was considered a useful addition in international TB outbreak investigations. Further standardization of the WGS methodology and good structures for international collaboration and coordination are needed to take full advantage of this new technology. Whether the use of WGS results in earlier detection of cases and thus limits transmission still needs to be determined.